Systemic autophagy in the therapeutic response to anthracycline-based chemotherapy - Castoldi, Francesca; Vacchelli, Erika; Zitvogel, Laurence; Maiuri, Maria Chiara; Pietrocola, Federico; Kroemer, Guido (Oncoimmunology, 2019)
The success of chemotherapy largely depends on the anticancer immune response triggered by tumor cells that succumb to immunogenic cell death (ICD). One of the hallmarks of ICD is premortem autophagy that facilitates the release of adenosine triphosphate from dying cancer cells and acts as a chemoattractant for dendritic cell precursors. Here, we show that the immune response induced by inoculation of cancer cells undergoing ICD in response to the anthracycline mitoxantrone (MTX) can be improved by a short-term fasting regimen (48 hours of starvation) and that this effect is reversed by systemic administration of the autophagy inhibitor dimethyl α-ketoglutarate. Tumor growth reduction by MTX treatment is known to depend on autophagy induction in cancer cells as well as on an intact immune system. We compared the antitumor effects of MTX on autophagy-competent cancers implanted in wild type (WT) or partially autophagy-deficient (Becn1± or Atg4b-/-) mice. While there was no difference in the tumor growth reducing effects of MTX on tumors evolving in WT, Becn1+/- and Atg4b-/- mice, we observed an increase in the toxicity of MTX on Atg4b-/- mice. These results suggest that autophagy in cancer cells (but less so in host cells) is rate-limiting for therapeutically relevant anticancer immune responses, yet has a major role in blunting the life-threatening toxicity of chemotherapy.
Keywords: immunotherapy; immunogenic cell death; Cancer; mitoxantrone; fasting